Semantic Roles of the Subject in Arabic Triliteral Verbal Clauses - Muhammad Habibie Alfath; Muhamad Saiful Mukminin (Translation and Linguistics (Transling), 2026)
This study investigates the semantic roles of subjects in Arabic triliteral verbs employing a grammatical semantic analysis framework. Unlike traditional assumptions, subjects in verbal clauses do not uniformly function as agents; instead, they manifest diverse semantic roles—including experiencer, patient, theme, and recipient—determined by the verb's specific vowel pattern. Adopting a qualitative methodology, primary data were extracted from Auzānu al-Af'āl wa Ma'ānīhā (Patterns of Verbs and Their Meanings) by Hasyim Taha Syalasy, a comprehensive reference on Arabic verbal morphology. Data collection utilized a documentation method, incorporating systematic observation and note-taking techniques to compile relevant verbal constructions. Subsequent analysis applied a distributional approach via immediate constituent analysis, facilitating precise classification of grammatical functions and semantic mappings. Key findings delineate semantic preferences across the six canonical vowel patterns of basic triliteral verbs: fa'ala–yaf'ulu and fa'ala–yaf'alu predominantly realize subjects as agents in transitive contexts; fa'ala–yaf'ilu, fa'ila–yaf'alu, and fa'ila–yaf'ilu exhibit experiencer or patient roles, often in psychological or perceptual predicates; while fa'ula–yaf'ulu consistently presents subjects as themes or experiencers within stative scenarios. These role assignments are modulated by factors such as verb transitivity, inherent lexical semantics, and the integration of embedded objects.